Association between Dental Caries and Obesity in Children and Young People: A Narrative Review - Abdulmonem A. Alshihri; Helen J. Rogers; Mohammed A. Alqahtani; Mohammed S. Aldossary (International Journal of Dentistry)
Objectives. To explore the association between obesity and dental caries in children and adolescents. Furthermore, to consider the possible reasons behind this relationship. Methods. A database search for papers published between January 2015 and May 2018, inclusive, addressing the association between obesity and dental caries was conducted. A review and critical appraisal of all included studies was performed. Results. Twenty-six studies were included in this review from different populations worldwide. Eight studies assessed the primary dentition, nine studies were conducted on permanent dentition, and remaining nine studies on both dentitions. The results regarding the association between obesity and dental caries were conflicting and inconsistent. Nine studies concluded that there was no relationship between obesity and dental caries. A positive association was reported in five studies, while the inverse association was reported in eleven studies. Studies included in this review had significant variations in methodology and the investigated cofactors. Possible explanations of the controversial association between obesity and dental caries are discussed in this review. Conclusion. Both obesity and dental caries are multifactorial diseases, and their association is far more complex that can be explained by a single common risk factor, presenting evidence for the complexity of this association.